2013
DOI: 10.1021/ja4084336
|View full text |Cite
|
Sign up to set email alerts
|

Alkahest for V2VI3 Chalcogenides: Dissolution of Nine Bulk Semiconductors in a Diamine-Dithiol Solvent Mixture

Abstract: The ability to solution deposit semiconductor films has received a great deal of recent attention as a way to potentially lower costs for many optoelectronic applications; however, most bulk semiconductors are insoluble in common solvents. Here we describe a novel and relatively nonhazardous binary solvent mixture comprised of 1,2-ethanedithiol and 1,2-ethylenediamine that possesses the remarkable ability to rapidly dissolve a series of nine bulk V2VI3 chalcogenides (V = As, Sb, Bi; VI = S, Se, Te) at room tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
187
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(197 citation statements)
references
References 29 publications
6
187
4
Order By: Relevance
“…We presented novel anodization protocol and photo-electrochemical results for anodic TiO 2 nanotubes grown with different diameter sizes (21,35, 56 and 95 nm) utilized as highly ordered n-type conductive scaffold for inorganic chromophore (Sn-S-Se). While downscaling the nanotube diameter significantly increased the number of nanotubes per square unit and thus the active surface area increased as well, we found that the photo-electrochemical response was identical and thus independent of the TiO 2 diameter nanotube size, but it correlated with the thickness of the nanotube layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We presented novel anodization protocol and photo-electrochemical results for anodic TiO 2 nanotubes grown with different diameter sizes (21,35, 56 and 95 nm) utilized as highly ordered n-type conductive scaffold for inorganic chromophore (Sn-S-Se). While downscaling the nanotube diameter significantly increased the number of nanotubes per square unit and thus the active surface area increased as well, we found that the photo-electrochemical response was identical and thus independent of the TiO 2 diameter nanotube size, but it correlated with the thickness of the nanotube layers.…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of organic dyes or organohalide perovskites, the absorbing chalcogenide layer can be deposited via a solvent solution process, i.e. a hydrazine-based [18][19][20] or a mixture of 1,2-ethylenediamine + 1,2-ethanedithiol-based 21 solutions. This process is amenable to infill or coat TiO 2 nanotube layers in order to form hybrid solar cells easily and cheaply.…”
Section: Introductionmentioning
confidence: 99%
“…Thin films of SnS were synthesized using literature procedures. [7][8] Briefly, bulk SnS powder was dissolved in 11:1 vol/vol mixture of ethylenediamine and 1,2-ethanedithiol at 50 °C for 15 h at a concentration of 60 mg mL -1 . Solutions were then filtered using a 0.45 µm filter and spin coated onto FTO substrates.…”
Section: Supporting Information Experimental Methodsmentioning
confidence: 99%
“…The severity of this situation is underscored by the fact that resistance to piperaquine, an ACT partner drug, is emerging in western Cambodia (8,9). No alternative, fully effective first-line therapy is currently available to replace ACTs, should ART fail globally.…”
Section: Acknowledgmentsmentioning
confidence: 99%